Teachers' Self-fulfilling Prophecy (SFP) Impacts Students' Disaster Preparedness - Purnama, Diana Septi; Kurniawan, Shopyan Jepri; Jayanti, Norma Nida (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Research to determine the effect of teachers' Self-fulfilling prophecy (SFP) on students' disaster preparedness, using a single-subject experimental design. The research design model AB. The number of research subjects was 8 students of Aviation Vocational High School Angkasa Ardhya Garini (AAG), Adisutjipto, Yogyakarta. Data collection used in this study used a disaster preparedness scale. Data were analyzed using descriptive statistics and gain score calculations. The average disaster preparedness score for the student group with teachers who had a positive Self-fulfilling prophecy (SFP) before the handling stage was 76.10; after the handling stage, it increased to 83.75. This shows an increase of 7.70 points. The average disaster preparedness score for the student group with teachers who had a negative self-fulfilling prophecy (SFP) before the handling stage was 77.20; after the handling stage, it increased to 79.58. This shows an increase of 2.40 points. The implication of this research is that teachers' self-fulfilling prophecy (SFP) increases students' preparedness for various natural disasters by optimizing guidance and counseling services. Keywords: disaster preparedness, self-fulfilling prophecy, students